Design Optimization on Cost Efficiency and Benefit Increase of Project Construction Unit Production PT.X - Muhammad Faisal Ghifari; Muhammed Ali Berawi (AIBPM Publisher, 2021)
The increased consumption of poultry in Indonesia, opening up greater business opportunities in the industry. The rapid project construction in the livestock business should be questioned whether the implementation of project has been carried out properly? The evaluation of production requirements, project design scenarios, the cost of project, and the value of every component that have been carried out should be identified by evaluating the requirements, specifications, standard quality, the machines and equipment. In the last 4 years, PT.X has built 4 new breeding farm units, in far different locations, typical layouts, land areas, varied building and installation designs. This resulted in the creation of master plan that was not standardized. By conducting an evaluation related to design optimization on the construction of the 4 PT X breeding farm unit, the better standard design is obtained in terms of cost and value. The research of the method done by analyzing the production needs as a scenario design that produce the parameter design as the reference in making the new standard design. The result of the optimization is an efficient cost with suitable function for the production and also giving some extra benefit by providing more facilities and utilities.